2015
DOI: 10.1155/2015/905204
|View full text |Cite
|
Sign up to set email alerts
|

Office Hysteroscopic Laser Enucleation of Submucous Myomas without Mass Extraction: A Case Series Study

Abstract: Background and Objectives. A new two-step hysteroscopic myomectomy carried out in the office setting and without anesthesia was feasible for the excision of submucous myomas. The objective of this study was to assess whether removal of submucous myomas from the uterine cavity after hysteroscopic laser enucleation is necessary. Methods. Between June 2009 and April 2013, all outpatients with symptomatic myomatosis (bleeding, pelvic pain, and infertility) assessed ultrasonographically were eligible to participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…These authors reported on further 61 patients with office hysteroscopic myomectomy, using a similar technique [14]. It is not clear whether the patients who were included in the previous report were included again in this second report, although there is overlap of the times of these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported on further 61 patients with office hysteroscopic myomectomy, using a similar technique [14]. It is not clear whether the patients who were included in the previous report were included again in this second report, although there is overlap of the times of these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…If the myoma remains enucleated and free in the uterine cavity, there are authors that advocate leaving it for spontaneous expulsion, in the Haimovich series (after laser myomectomy) the median duration to expulsion being 68 days, with no complication [5].…”
Section: Limits For Office Hysteroscopic Myomectomymentioning
confidence: 99%
“…The incidence of infection following operative hysteroscopy varies between 0.01 [5] and 1.42% [32]. Prevention of infection may be possible by reducing the duration of the intervention.…”
Section: Complicationsmentioning
confidence: 99%
“…Dr. Sergio Haimovic from Spain presented the feasibility of a new two-step technique for office hysteroscopic resection of submucous myomas, by office laser treatment [34]. He enrolled patients in reproductive age with symptomatic lesions sonographically diagnosed as single mainly intracavitary (G1 or G2) myoma <4.0 cm, Patients underwent a two-step hysteroscopic procedure, which included preparation of partially intramural myomas with incision of the endometrial mucosa and the pseudocapsule covering the myoma in the first step, and excision of the myoma by means of diode laser four weeks later.…”
Section: Dr David Chuderland From Genesort Ltdmentioning
confidence: 99%